Internet of Things Based Automatic Heigh Detection with Ultrasonic Sensor: Using SMS Gateway for Detection Information - April Firman Daru (Universitas Kristen Satya Wacana, 2022)
Man-made fish pond is an artificial pond filled with brackish water and located near seawater border to allow mixing with fresh water. These ponds were used as aquaculture for fish, shrimp, shellfish, and others. The success factors are determined by the quantity of brackish water in the pond. If the seawater level not reached 25cm-30cm above normal level, then the seawater can't be flowed into the river. In order to solve the problem, an Internet of Things based model is proposed to assist the onwer to obtain the seawater level information. This research utilized Arduino Uno microcontroller to control the sensor and communication module. This model able to send messages to owner in realtime. The main purpose of this model is to help fish pond owner to get seawater information easily without checking directly.